Memorandum of Understanding between the BRAC University and Liverpool School of Tropical Medicine, Pembroke Place, Liverpool (2009) - James P. Grant School of Public Health, BRAC University; Leverpool School of Tropical Medicine, Liverpool (BRAC University and Liverpool School of Tropical Medicine, 2013)
Non disclosure and exclusivity agreement made on the 12th day of May, 2009 (agreement date) between 1. BRAC University, 66 Mohakhali, Dhaka 1212, ("BRAC"), hereafter referred to as the receiving party; and 2. the Liverpool School of Tropical Medicine, Pembroke Place, Liverpool, L3 SQA ("LSTM"), hereafter referred to as the disclosing party.